The reachable 3-D workspace volume is a measure of payload and body-mass-index: A quasi-static kinetic assessment - Castro, Miguel Nobre; Rasmussen, John; Bai, Shaoping; Andersen, Michael Skipper (Applied ergonomics, 2019)
An experimental protocol with five tasks is proposed for a low-cost empirical assessment of the reachable 3-D workspace (RWS), including both close-to-torso and far-from-torso regions. Ten participants repeated the protocol for four distinct hand payloads. The RWS expressed as a point cloud and its non-convex alpha-shape were obtained for each case. Moreover, individual strength surrogates for glenohumeral flexion and abduction, and elbow flexion were collected using a dynamometer. The RWS volume was statistically modelled using payload, body-mass-index and the strength surrogates as predictors. For increasing payload, a significant (r = −0.736,p < 0.001) decrease in RWS volume was found for distinct payload cases across all subjects. The only significant predictors found for the RWS volume were normalized payload (F = 73.740,p < 0.001) and body-mass-index (F = 11.008,p = 0.003). No significant interactions were found. The consequent regression model (F(2,27) = 41.11, p < 0.001, Radj2 = 0.7345) explained around 73% of the variation in the data. The RWS volume is a function of payload and body-mass-index. [Display omitted] •A new experimental protocol is proposed for assessing the reachable 3-D workspace.•Alpha-shapes enable retrieval of the non-convex shape of all reachable envelopes.•The reachable 3-D workspace volume inversely correlates to payload.•Payload and body-mass-index predicted 73% of the variation in the RWS volume.